Предмет:
МатематикаАвтор:
анонима) f(x) = x^3 - 10x^2 + 5x + 1 ;
Формулы для нахождения производной: (x^a) = a × x^a-1 ; производная числа = 0 ;
Следовательно: f\'(x) = 3x^2 - 20x + 5 ;
б) f(x) = 2 / x^7 + 4√3 ;
Формула: (a / g)\' = a\' × g - a × g\' / g^2 ;
f\'(x) = 0 × x^7 - 2 × 7x^6 / x^14 + 0 = - 14x^6 / x^14 ;
в) f(x) = (5x^2 + 2) × √x ;
Формула: (a × b)\' = a\' × b + a × b\' ; производная √x = 1 / 2√x ;
f\'(x) = 10x × √x + (5x^2 + 2) × 1 / 2√x = 10x × √x + 5x^2 + 2 / 2√x .
Автор:
isabelleДобавить свой ответ